2002
DOI: 10.4141/p01-044
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and N benefits to sequential wheat and barley crops from single-year alfalfa, berseem and red clover, chickling vetch and lentil

Abstract: Grain yield and N benefits to sequential wheat and barley crops from single-year alfalfa, berseem and red clover, chickling vetch and lentil. Can. J. Plant Sci. 82: 53-65. Singleyear hay alfalfas (Medicago sativa L.), berseem (Trifolium alexandrinum L.) and red clovers (Trifolium pratense L.), chickling vetch (Lathyrus sativus L.) and lentil (Lens culinaris Medik.) were evaluated for rotational yield and N benefits to the following first-year wheat (Triticum aestivum L.) and second-year barley (Hordeum vulgare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Fall rye biomass production ranged from 6290 to 7670 kg ha À1 and grain yield ranged from 3160 to 3640 kg ha À1 . Bullied et al (2002) also reported no effect from a low N single year green manure to the second grain crop. Similar to what was observed in the wheat year, N "stored" in catch crop biomass did not benefit fall rye productivity.…”
Section: [ ( F I G _ 2 ) T D $ F I G ]mentioning
confidence: 89%
“…Fall rye biomass production ranged from 6290 to 7670 kg ha À1 and grain yield ranged from 3160 to 3640 kg ha À1 . Bullied et al (2002) also reported no effect from a low N single year green manure to the second grain crop. Similar to what was observed in the wheat year, N "stored" in catch crop biomass did not benefit fall rye productivity.…”
Section: [ ( F I G _ 2 ) T D $ F I G ]mentioning
confidence: 89%
“…Bullied et al (2002) found greater grain yield, protein content, and grain N yield in second-crop barley grown after single-year alfalfa stands (alfalfa was seeded in spring, hayed twice during the summer and incorporated in the fall) compared with second-crop barley grown after canola or fallow controls. Long-term N and non-N benefits of alfalfa to following crops have been reported by many workers (Ladd et al 1985;Janzen et al 1990;Hoyt 1990;Janzen and McGinn 1991).…”
Section: Nitrogen Use Efficiencymentioning
confidence: 97%
“…This indicates that mulch-supplied N was the source of increased second-year oat yields in the mulched plots. Other workers have also found positive N uptake benefits for multiple years in crops grown after incorporation of alfalfa residues (Bullied et al 2002).…”
Section: Second-year N Uptake and Yield Of Oatmentioning
confidence: 99%
“…The interest of growing legumes has been increasing with the rising price of N fertilizers (Bullied et al 2002). In legume-non-legume crop sequences, the amount of N fertilizer that can be replaced depends on:…”
Section: Cropping Systemsmentioning
confidence: 99%